Details of force transmission at the handle - Kleshnev, V. (BioRow, 2022)
Here we continue discussing force transmission at the handle started in the previous Newsletter (RBN 2022/12). The effects of two factors will be analysed: 1) stroke rate, 2) blade type. The data was obtained using the BioRow 4D instrumented handle in a M1x doing a step-test (1min x 20, 25, 30 and 35spm) repeated with three blade types: Comps, Fat2 and Smoothies.